The Effects of Zinc Oxide nanoparticles synthesized from Eucalyptus plant extracts against mealworm stages Tenebrio molitor L., 1758 (Tenebrionidae: Coleopetera) - Omar, Saher Taher; Ali, Wand Khalis; Karim, Ayoub Sabir (Tikrit Journal of Pure Science, 2023)
Despite the widespread utilization of Zinc Oxide nanoparticles (ZnO NPs) in different areas, there have been several studies regarding their toxicity. Thus, this study aimed to produce zinc oxide nanoparticles using a simple and eco-friendly biosynthesis process, utilizing the Eucalyptus (Eucalyptus camaldulensis Dehn.) as a reducing agent. It also aimed to estimate their insecticidal efficacies toward the mealworm's stages (Tenebrio molitor L.,1758(. The produced ZnO nanoparticles were characterized by X-ray diffraction, UV–visible, and transmission electron microscopy (TEM). The laboratory experiment was carried out with one way of exposure, using the feeding method through immersing the leaf in ZnO NPs solution with different concentrations. The mortality effects on insect's stages were recorded in various periods of time. The statistical analysis results indicated the presence of noteworthy variations in the average mortality rate according to insect's stage, showing a different effect on the average of larval mortality rate. In this regard, the highest average of larval mortality rate was recorded at 5000ppm (61.25%); while the general average percentage of adult emergence was (42.53%). After three weeks, the highest general mean of adult mortality was obtained at 5000ppm (87.48%). Similarly, the LC50 value of the ZnO NPs derived from the used plant extract against the larval stage was (3630.78 ppm). This result revealed that Zinc Oxide Nanoparticles from plant extract sources have both larvicidal and adulticidal properties and they could serve as an eco-friendly alternative to synthetic insecticides for controlling insect's stages. Hence, the biogenic Zinc Oxide Nanoparticles can be used as a potential bio-insecticidal agent for the future.